(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
Ignazio Guidi (Rome 1904 – Rome 1978) was an architect and an urbanist and his work, until today, is almost unknown. His production collects a number around a hundred of projects, from the field of architecture to the urbanism, partially documented in his private archive and quoted in some of the manuals/guide on the city of Rome and in specialized journals. One of his major contribute is represented by his approach to the developing of the city. Guidi got his architecture degree at the University of Rome in 1929 and, on July 1934, he got the master in urbanism. He will be involved in the urbanistic asset of Rome from his first collaboration for the 1931 Urban Plan as Cesare Valle assistant, passing through his collaboration for the design of the “Piano delle Arterie di Scorrimento” to his role of responsibility as Head Architect for the 1962 Urban Plan. He will be constantly in relationship with the construction of the city of Rome and next to it he will develop thoughts, ideas and projects around the urban plan topic which will be part of his professional life, picturing a kind of manner of making city. This manner is declined by his major subjects of interest and investigation: the relationships within the parts, the architectonical elements, and the shape of the public space. Through the analysis of four project of Ignazio Guidi, the essay try to offer and analyze the author point of view regarding the conformation of the square and the construction of the urban spaces.